Estudio de prefactibilidad para la instalación de una planta de habilitación de viviendas prefabricadas - Cock Guerrero, Diego André (2020)
This project's main goal is to determine the technological, economic, financial, commercial and social feasibility of an assembly plant for prefabricated houses built with drywall and galvanized steel. These houses have shorter construction times, lower prices and have aseismic properties in contrast with traditional built houses; those characteristics are well received in our target market, which consists of low-income citizens. This statement can be reflected in the survey we conducted. We gathered data on the loans made through MiVivienda in the last years and we were able to determine a demand of 52 social houses for the first year, considering psychographic and demographic segmentation. The project’s location was chosen having in account factors such as the proximity to the target market, existing infrastructure, and workforce availability. Villa El Salvador was the best option among the analyzed districts. The size of the project was determined by the market size. To be able to reach the break-even point, we have to sell 40 houses. Moving on to the economic and financial evaluation, S/ 282 000 is the required investment, from which S/ 85 000 are financed through a financial institution over a 3-year period. The results were a three years investment recovery period, NPV of S/ 254 223 and a 57,91% IRR. Our sensitivity analysis determined that the price and the direct costs were the most sensible variables. The aggregate value on the final year of the project is S/ 9MM which reflects that materials gain a lot of value during the construction process. We also obtained that for every employee, an investment of S/ 13 429 is required.